Postmenopausal woman with vaginal mass: do not forget to see for uterine inversion. (13th August 2012) - Darji, Parth; Banker, Hiral; Gandhi, Viplav; Thakkar, Gurudatt
Abstract : Inversion of the uterus is a rare clinical problem. It is encountered as an obstetric emergency and is a diagnostic challenge in gynaecology. Non-puerperal inversion usually results from a tumour implanted on fundus of the uterus. Treatment depends on the associated pathology and the stage of the inversion. A rare case of non-puerperal uterine inversion caused by a large fundal submucous fibroid in a 58-year-old woman resulting in lower abdominal pain and vaginal bleeding was reported. After removal of fibroid, reduction of the inversion was successful and then abdominal hysterectomy was performed.